Monitoring Daily QA 3 constancy for routine quality assurance on linear accelerators. Issue 11 (November 2016) - Binny, Diana; Lancaster, Craig M.; Kairn, Tanya; Trapp, Jamie V.; Crowe, Scott B.
Highlights: Characterisation of Daily QA 3 for measured beam parameters, output, symmetry, flatness and energy. Independent temperature-pressure factor comparisons for Daily QA 3. Recommendations for clinical use. Abstract: The purpose of this study was to evaluate the suitability of the Daily QA 3 (Sun Nuclear Corporation, Melbourne, USA) device as a safe quality assurance device for control of machine specific parameters, such as linear accelerator output, beam quality and beam flatness and symmetry. Measurements were performed using three Varian 2300iX linear accelerators. The suitability of Daily QA 3 as a device for quality control of linear accelerator parameters was investigated for both 6 and 10 MV photons and 6, 9, 12, 15 and 18 MeV electrons. Measurements of machine specific using the Daily QA 3 device were compared to corresponding measurements using a simpler constancy meter, Farmer chamber and plane parallel ionisation chamber in a water tank. The Daily QA 3 device showed a linear dose response making it a suitable device for detection of output variations during routine measurements. It was noted that over estimations of variations compared with Farmer chamber readings were seen if the Daily QA 3 wasn't calibrated for output and sensitivity on a regular eight to ten monthly basis. Temperature-pressure correction factors calculated by Daily QA 3 also contributed towards larger short term variations seen in output measurements. Energy, symmetry and flatness variations detected by Daily QA 3 were consistent with measurements performed in water tank using a parallel plate chamber. It was concluded that the Daily QA 3 device is suitable for routine daily and fortnightly quality assurance of linear accelerator beam parameters however a regular eight-ten monthly dose and detector array calibration will improve error detection capabilities of the device.